Internalisasi Kearifan Lokal Budaya Gegunungen Masyarakat Teluk Rumbia Kecamatan Singkil Kabupaten Aceh Singkil - Rina Auliana; Sri Listiana Izar (Medan Resource Center, 2023)
His study aims to determine the local cultural wisdom of the Teluk Rumbia community. The cultural values ??of the Gunung-gunungan ceremony carried out by the Acehnese people of the Singkil tribe to the community have three value aspects, namely moral aspects, social aspects, and aspects of faith or divinity. The data sources in this research use primary data and secondary data. Sources of data taken in this study is data taken directly by researchers through direct observation and interviews. The data analysis technique used in this study is an interactive analysis technique.